2021
DOI: 10.1021/acs.oprd.0c00345
|View full text |Cite
|
Sign up to set email alerts
|

API Continuous Cooling and Antisolvent Crystallization for Kinetic Impurity Rejection in cGMP Manufacturing

Abstract: Crystallization of 204 kg of final active pharmaceutical ingredient was accomplished continuously using a cascade of mixed suspension mixed product removal crystallizers in cGMP manufacturing. This article describes the journey taken to transform a set of technical to final batch crystallizations into a continuous, combined cooling and antisolvent crystallization using three stirred tank crystallizers in series. Conversion of the batch process to a continuous process was beneficial to kinetically purge a key i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 68 publications
0
25
0
Order By: Relevance
“…Thereby, a strategy of switching filter plates is realized for a quasi-continuous filter cake discharge. Since their work focused on end-to-end manufacturing, the individual effect of the filter on product quality was not investigated in detail …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thereby, a strategy of switching filter plates is realized for a quasi-continuous filter cake discharge. Since their work focused on end-to-end manufacturing, the individual effect of the filter on product quality was not investigated in detail …”
Section: Introductionmentioning
confidence: 99%
“…Since their work focused on end-to-end manufacturing, the individual effect of the filter on product quality was not investigated in detail. 23 To overcome the stated open issues, we developed and patented the small-scale continuous vacuum screw filter (CVSF) for continuous particle isolation from suspensions in small-scale for volume flow rates between 10−100 mL min −1 . 24 Our first study showed that the PSD was entirely maintained during filtration, and a narrow residence time distribution of solid phase (RTD S ) is ensured.…”
Section: Introductionmentioning
confidence: 99%
“…The probable cause of reduced dissolution in DMSOte and NMPate might be due to the impurities formed upon degradation (DMSO boiling point 462.15 K, NMP boiling point 475.15 K) compared to dioxanate and THPate, as those GLN solvates decomposed at 473.74 K and 469.53 K respectively which were close to the Form I decomposition peak (489.15 K) [4]. Even a small amount of impurity in the slurry could impede polymorphic stability [42]; however, the degradation of the solvates kept at 40 • C and 75% RH for 30-day, had less than 1.5% impurity, indicating a high degree of purity of the GLN solids with respect to impurities and degradation products [43]. Previously, GLN binary mixture gave more hydrophilic structure of the crystal surface compared to GLN reference (dissolution of X G = 0.3, 0.5 or 0.7 > dissolution of X G = 1) which increased its wettability and contributed to improved dissolution [7].…”
Section: Tableting Of Gln Solvate In Vitro Dissolution Study and Stab...mentioning
confidence: 54%
“…However, this can be achieved by final-product purification using techniques such as multicolumn chromatography catch-and-release chromatography, simulated moving bed (SMB), crystallisation, recrystallisation and centrifugal partition chromatography (CPC). 51,54–59 Adding to scalability concerns of some of these purification methodologies, these techniques have their drawbacks; crystallization and recrystallisation usually requires semi-batch processing, catch-and-release chromatography needs automated multiple columns switching and the SMB chromatography operation is technically complex and it uses expensive absorbents. 12,51,60 The application of various downstream continuous flow processing strategies examples are reviewed herein.…”
Section: Continuous-flow Downstream Processingmentioning
confidence: 99%